ナンキョク ニオケル ウチュウ ブッシツ ニ カンスル ケンキュウ IV ヤマト インセキ ニ ツイテ - 島, 誠; シマ, マコト; 岡田, 昭彦; オカダ, アキヒコ; 島, 正子; シマ, マサコ; SHIMA, Makoto; OKADA, Akihiko; SHIMA, Masako (国立極地研究所, 1974)
P(論文) Additional mineralogical and chemical studies of the Yamato meteorites are under way. The mode analysis and the optical properties in thin sections are examined under a microscope. Chondrites occur in all of the Yamato meteorites with the exception of Yamato (b). Yamato (a) is composed mainly of pyroxene, olivine and opaque minerals (iron phase, sulphide phase, etc.). Pyroxene occurs as enstatite (En_<98>) and olivine as forsterite (Fo_<95>). Yamato (b) is composed mainly of pyroxene of En_<74>Fs_<26> composition. Yamato (c) is composed of olivine and opaque minerals containing carbon compounds; olivine has the composition of Fo_<60> Fa_<40>. Yamato (d) is composed of olivine, pyroxene and opaque minerals; olivine has the composition of Fo_<90>Fa_<10> and pyroxene the composition of En_<85>Fs_<15>. Some chondrules in these meteorites are distinguished by their particular mineral composition. The chemical compositions of the Yamato meteorites were determined by the wet chemical analysis. From 0.5 g aliquots of powdered samples, several fractions were taken out by the fractional dissolution method. Yamato (a) contains much metallic iron, water-soluble calcium sulphide (oldhamite) and only acid insoluble silicates. Yamato (b) contains essentially no metallic iron or nickel, but is high in Si and Mg. Yamato (c) has an extremely small concentration of metallic iron whereas total iron is very high. This iron consists mainly of magnetite. Yamato (d) is a high iron chondrite group. The trace elements, W, Re, Os, Ir, Pt, Au, Hg, Tl, Bi, Th and U, were determined utilizing a spark source mass spectrograph MS7 with electrical ion detection. The abundance distribution patterns of the trace elements confirm the result of the already classified reference meteorites. The solidification ages of the Yamato meteorites were determined by the K-Ar method. Yamato (a), (b), (c) and (d) are estimated to be 2.3, 4.4, 12.2 and 15.4×10^7 yr. respectevely. By these ...